Efficient and stable emission of warm-white light from lead-free halide double perovskites. (22nd November 2018) - Luo, Jiajun; Wang, Xiaoming; Li, Shunran; Liu, Jing; Guo, Yueming; Niu, Guangda; Yao, Li; Fu, Yuhao; Gao, Liang; Dong, Qingshun; Zhao, Chunyi; Leng, Meiying; et al.
Abstract Lighting accounts for one-fifth of global electricity consumption1 . Single materials with efficient and stable white-light emission are ideal for lighting applications, but photon emission covering the entire visible spectrum is difficult to achieve using a single material. Metal halide perovskites have outstanding emission properties2, 3 ; however, the best-performing materials of this type contain lead and have unsatisfactory stability. Here we report a lead-free double perovskite that exhibits efficient and stable white-light emission via self-trapped excitons that originate from the Jahn–Teller distortion of the AgCl6 octahedron in the excited state. By alloying sodium cations into Cs2 AgInCl6, we break the dark transition (the inversion-symmetry-induced parity-forbidden transition) by manipulating the parity of the wavefunction of the self-trapped exciton and reduce the electronic dimensionality of the semiconductor4 . This leads to an increase in photoluminescence efficiency by three orders of magnitude compared to pure Cs2 AgInCl6 . The optimally alloyed Cs2 (Ag0.60 Na0.40 )InCl6 with 0.04 per cent bismuth doping emits warm-white light with 86 ± 5 per cent quantum efficiency and works for over 1, 000 hours. We anticipate that these results will stimulate research on single-emitter-based white-light-emitting phosphors and diodes for next-generation lighting and display technologies. After alloying with metal cations, a lead-free halide double perovskite shows stable performance and remarkably efficient white-light emission, with possible applications in lighting and display technologies.